CONTEXTUAL APPROACH IN PSYCHOLOGY - Verbitsky, A.A.; Kalashnikov, V.G. (European Scientific Journal, ESJ, 2013)
The article contains a brief review of the concept «context» which is becoming one of key concepts of modern theoretical and empirical psychology. On the basis of the analysis of the scientific literature the authors allocate two complementary understandings of the context – structural (a fragment of the text as a semantic system) and functional (generation of sense mental mechanism). The authors suggest understanding mentality as a recursive-contextual phenomenon in which each fragment of its maintenance exists in the context of previous fragments and represents the context for fragments of the subsequent. Such understanding can become a basis of the contextual approach in psychology.